(untitled) (Archives of Mechanics - Test, 2001)
This paper deals with the application of 3D-constitutive models for concrete to simulations of pull-out experiments [1]. Two different models are considered: • The first material model is formulated within the framework of multi-surface plasticity. It consists of three Rankine yield surfaces for the simulation of cracking and a Drucker-Prager yield surface for the description of compressive failure of concrete. The Drucker-Prager surface is reformulated in order to account for the influence of confinement on the compressive strength and the ductility of concrete. • The formulation of the second model, the Extended Leon Model (ELM) [4], is based on one yield function for description of compressive and tensile failure of concrete. It accounts for the influence of the Lode angle on the material strength. The simulation of ductile behavior of concrete is controlled by means of a pressure-dependent ductility function. The predictive capability of the models is demonstrated by means of a finite element (FE) analysis of a pull-out test [1]. The influence of confinement on the peak load and the failure mode is investigated.